Adverse events in orthopedic care identified via the Global Trigger Tool in Sweden – implications on preventable prolonged hospitalizations. Issue 1 (December 2016) - Rutberg, Hans; Borgstedt-Risberg, Madeleine; Gustafson, Pelle; Unbeck, Maria
Abstract Background The national incidence of adverse events (AEs) in Swedish orthopedic care has never been described. A new national database has made it possible to describe incidence, nature, preventability and consequences of AEs in Swedish orthopedic care. Methods We used national data from a structured two-stage record review with a Swedish modification of the Global Trigger Tool. The sample was 4, 994 randomly selected orthopedic admissions in 56 hospitals during 2013 and 2014. The AEs were classified according to the Swedish Patient Safety Act into preventable or non-preventable. Results At least one AE occurred in 733 (15 %, 95 % CI 13.7–15.7) admissions. Of 950 identified AEs, 697 (73 %) were judged preventable. More than half of the AEs (54 %) were of temporary nature. The most common types of AE were healthcare-associated infections and distended urinary bladder. Patients ≥65 years had more AEs (p < 0.001), and were more often affected by pressure ulcer (p < 0.001) and urinary tract infections (p < 0.01). Distended urinary bladder was seen more frequently in patients aged 18–64 years (p = 0.01). Length of stay was twice as long for patients with AEs (p < 0.001). We estimate 232, 000 extra hospital days due to AEs during these 2 years. The pattern of AEs in orthopedic care was different compared to other hospital specialties. Conclusions Using a national database, we found AEs in 15 % of orthopedic admissions. The majority of the AEs was of temporary nature and judged preventable. Our results can be used to guide focused patient safety work.